Farocki/Godard : Film as Theory - Pantenburg, Volker, 1973- (Schriften des Internationalen Kollegs für Kulturtechnikforschung und Medienphilosophie, 2019)
This book brings together two major filmmakers--German avant-gardist Harun Farocki and French New Wave master Jean-Luc Godard--to explore the fundamental tension between theoretical abstraction and the capacities of film itself, a medium where everything seen onscreen is necessarily concrete. Volker Pantenburg shows how these two filmmakers explored the potential of combined shots and montage to create "film as theory."